The Immune-Modulator Pidotimod Affects the Metabolic Profile of Exhaled Breath Condensate in Bronchiectatic Patients: A Metabolomics Pilot Study - D’Amato, Maria; Paris, Debora; Molino, Antonio; Cuomo, Paola; Fulgione, Andrea; Sorrentino, Nunzia; Palomba, Letizia; Maniscalco, Mauro; Motta, Andrea (Frontiers in Pharmacology, 2019)
Pidotimod, a synthetic dipeptide molecule with biological and immunological activity, is used to reduce the number of exacerbations or pneumonitis in patients with inflammatory diseases. In the present study, we investigated whether Pidotimod modifies the metabolomic pathways measured in the exhaled breath condensate (EBC) of non-cystic fibrosis bronchiectatic patients (NCFB). We analyzed 40 adult patients affected by NCFB. They were randomized to receive Pidotimod 800 mg b/d for 21 consecutive days (3 weeks) a month for 6 months (20 patients, V1 group) or no drug (20 patients, V0 group), with a 1:1 criterion, followed as outpatients. EBC samples were collected from all patients at baseline and after 6 months. They were investigated by combined nuclear magnetic resonance (NMR) spectroscopy and multivariate statistical analysis to uncover metabolic differences between EBC from NCFB patients before and after therapy with Pidotimod. Pulmonary function test and pulmonary exacerbations were analyzed at baseline and at the end of Pidotimod therapy. The EBC metabolites were all identified, and through statistical evaluation, we were able to discriminate the two samples’ classes, with acetate, acetoin, lactate and citrate as statistically significant discriminatory metabolites. The model vas validated by using a blind set of 20 NCFB samples, not included in the primary analysis. No differences were observed in PFT after 6 months. At the end of the study, there was a significant decrease of exacerbation rate in V1 group as compared with V0 group, with a substantial reduction of the number of mild or severe exacerbations (p < 0.001). Pidotimod modifies the respiratory metabolic phenotype (‘‘metabotype’’) of NCFB patients, and reduces the number of exacerbations.